The conductivity of Li₂Fₑ0₂ and Li₃Fₑ0₃ / Mohd Adib Abdul Hamid - Abdul Hamid, Mohd Adib (2011)
The development of portable equipment such as personal computers, mobile phones, and others has an increasing in demand for battery power sources. Lithium batteries have been investigated as batteries which have high energy density. There is an invention involving lithium-iron-oxide as an electrode active material. It exhibited good cyclability delivering about 12mAh/g after 500 deep charge/ discharge cycle. Lithium iron oxide having a tunnel structure that can cause electrochemical intercalation and deintercalation of lithium ion in any lithium conductive electrolyte. Purity of the material is determined by using X-ray powder diffraction pattern. The conductivity testing was run using WEIS510 impedance spectroscopy. The resistivity result from the impedance spectroscopy is vary in temperature from 60 °C to 100 °C. It is found that Li3Fe03 is more conductive than Li₂Fₑ0₂ and Li₃Fₑ0₃ is more conductive than Li₂Fₑ0₂ due to extra ions carrier. The conductivity of Li₃Fₑ0₃ is the movement of 3Li+ and [Fe03] ₋ ions and Li2Fe02 is the movement of 2Li+ and [Fe02] ₋ ions. Ionic exchange between cation and anion will determine the conductivity rate of the materials. Both materials are showing good conducting behaviour above 100°C and beyond.